Cyber crime concept and ways to prevent it (Numerus academy review, 2026)
Modern means of communication are considered one of the most important features of the current era, the era of technology and digital, as it facilitated manytransactions for all of humanity, as it brought the distant and shortened the times and facilitated communication between them, but some took advantage of this technology forcriminal purposes or what is known as electronic or cyber crimes. Technology andtechnology are witnessing many developments and the development of new things, and this portends the development of cybercrime tools and methods in a more complex ormore harmful way than before, which obliges countries to develop mechanisms to combatthese crimes. In this article, we will discuss the concept of cybercrime, the social andpsychological reasons for perpetrating these crimes, and ways to combat and prevent them.